Pengaruh Kandungan Cu dalam Air Irigasi terhadap Pertumbuhan dan Produksi Padi (Oryza sativa L.) - Sulistyono, Eko; Rokhmah, Fatkhiyatur (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
The research was conducted to investigate the effect of copper (Cu) levels in irrigation water on the growth and production of rice variety IR64. The experiment was arranged in randomized complete block design with six replications. The Cu treatments were: 0, 300, 600 and 900 mg Cu L-1of irrigation water. The results showed that Cu content significantly decreased rice growth and production. Copper level of 600 mg L-1 decreased plant height, tiller number and leaf number. Copper level of 300 mg L-1 decreased panicle length, number of grains per panicle, empty grain weight, 100 grains weight, milled grain weight, and shoot dry weight. This experiment implies that remediation treatments should be considered when Cu level in irrigation water was more than 300 mg Cu L-1. Copper level of 300 mg L-1 could be used as a critical level for rice screening for Cu tolerant varieties in the plant breeding program. Keywords: copper toxicity, low land rice, rice growth and production, water quality